(untitled) (IIUC Studies, 2026)
Blended learning gained huge scholarly attention in Bangladesh during and after the COVID-19 pandemic. Online teaching with tech-mediated tools was the only solution during the pandemic. Though it was the emergency response to continue teaching and learning during the disruptive situation, it paved the way to practice blended learning with the combination of face-to-face and online instruction. This paper reviews previously published literature, especially newspapers focusing on the pandemic and higher education in Bangladesh and accumulates students’ voices to identify innovative techniques practiced during the pandemic so that these can be utilized to form a blended learning approach. Focusing on the qualitative approach, data were collected through published literature and students’ interviews. Data from published materials were analyzed using the document analysis procedure, whereas data gathered from interviews were analyzed using the thematic analysis procedure. Findings highlight both the failure and success stories along with the way of utilizing those success stories to implement blended learning. Based on the findings focusing on innovative COVID practices, this study, drawing the attention of the relevant policymakers, presents a blended lesson plan that can be utilized for English language teaching in Bangladeshi higher educational institutions. IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 131-148